Phytochemical screening and evaluation of biological activity of Calligonum polygonoides L. subsp. comosum - Hayam S. Ahmed, Abeer S. Moawad, Asmaa I. Owis, Sameh F. AbouZid, Rehab F. Abdel-Rahman (Journal of Applied Pharmaceutical Science, 2015)
Calligonum polygonoides L. subsp. comosum; locally known as “arta”, is tall woody shrub, perennial desert plant. TLC screening, estrogenic and antimicrobial activities of different fractions of hydroalcoholic extract of the leaves; n-hexane, CH2Cl2, EtOAc and n-BuOH, were studied in order to find the correlation between the phytoconstituents and the biological activity. Estrogenic activity was studied in immature ovariectomized female Wistar rats by oral administration of 75 and 150 mg extract/kg body weight for seven days using 1 µg estradiol/rat/day as positive control. The antimicrobial activity against Aspergillus fumigatus, Candida albicans, Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Klebsiella pneumonia was carried out using agar diffusion method with determination of the minimum inhibitory concentration (MIC). The CH2Cl2 fraction showed significant estrogenic and antimicrobial activity by significantly increasing uterine weight and low MIC values for all tested microorganisms ranging from 0.03 and 3.9 mg/mL. The n-hexane fraction showed mainly the presence of sterols and/or triterpenoids. The EtOAc and n-BuOH fractions were the richest in flavonoids while that of methylene chloride was found to contain both classes of chemical compounds. In conclusion; flavonoids, sterols and/or triterpenes exhibit synergistic effect to the antimicrobial and estrogenic activity of Calligonum polygonoides leaves.
Keywords: Calligonum polygonoides, TLC screening, estrogenic, antimicrobial.